Pengembangan panduan model konseling cognitive behavioral therapy teknik mindfulness berbasis website SI-konseling untuk mengatasi traumatik pada remaja korban kekerasan - Prabayanti, I Dewa Agung Ayu Arisma; Suranata, Kadek; Dharmayanti, Putu Ari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The study aims to develop the validity and effectiveness of the cognitive behavioral therapy counseling model guide for mindfulness techniques based on the SI-Counseling website to overcome trauma in adolescent victims of violence. This research is included in development research with the 4D method (Define, Design, Develop, Disseminate). Data collection was carried out with an expert validity assessment which was analyzed using the CVR (Content Validity Ratio), CVI (Content Validity Index) and t-test formulas. The results of the CVR analysis show that all statements are on average relevant, the CVI score of 1 is in the very suitable category, and the cognitive behavioral therapy counseling model guide for mindfulness techniques has met the requirements for use. These results state that the development of a cognitive behavioral therapy counseling model guide for mindfulness techniques based on the SI-Counseling website is effective for overcoming trauma in adolescent victims of violence